Association Between Fast Food Consumption Patterns and Adolescent Obesity - Anita Lontaan; Lingga Puspita Sari; Nia Budhi Astuti (CV. Get Press Indonesia, 2025)
High consumption of fast food among adolescents is a serious concern because it has the potential to increase the risk of obesity. Lifestyle changes, lack of physical activity, and easy access to fast food exacerbate this situation. Purpose: The purpose of this study is to ascertain how fast food eating habits relate to the prevalence of adolescent obesity. Methods: The study employed a cross-sectional methodology and an analytical quantitative design. 75 teenagers between the ages of 15 and 18 who were chosen by purposive sampling at a single Padang City high school made up the sample. Body mass index (BMI) measurements and questionnaires on dietary patterns were used to gather data. Results: The chi-square test analysis revealed a significant correlation (p < 0.05) between the incidence of obesity and the frequency of fast food consumption. Teenagers who eat fast food three times a week are more likely to become obese than those who don't. Implications: the implication of this study is the need for educational interventions on healthy eating among adolescents, as well as the involvement of schools and families in controlling access to fast food. Conclusion: In conclusion, fast food consumption habits and obesity are significantly correlated, so prevention from school age is an important step in reducing the risk of long-term obesity.